Does misuse lead to a disorder? The misuse of prescription tranquilizer and sedative medications and subsequent substance use disorders in a U.S. longitudinal sample - Boyd, CJ (Addict Behav, 2017)
OBJECTIVES: We used two waves of National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) data and examined whether the misuse of prescription tranquilizers or sedatives at Wave 1 was associated with either continued misuse, tranquilizer/sedative use disorder, or other substance use disorder (SUD) at Wave 2. METHODS: Prospective data were analyzed from structured diagnostic interviews using the Alcohol Use disorders and Associated Disabilities Interview Schedule: DSM-IV Version (AUDADIS-DSM-IV). A nationally representative sample of 34,653 of U.S. adults, 18 years or older at Wave 1 (2001–2002), were re-interviewed at Wave 2 (2004–2005). After applying the survey weights, the sample represented a population that was 52% female, 71% White, 12% Hispanic, 11% African American, 4% Asian and 2% Native American or other. RESULTS: An estimated 79% of adults who engaged in tranquilizer or sedative misuse at Wave 1 had stopped using these drugs at Wave 2. Only a small percentage (4.3%) of misusers at Wave 1 had a tranquilizer or sedative use disorder at Wave 2. However, forty-five percent (45.0%) of misusers at Wave 1 had at least one other SUD at Wave 2. Among those in remission from a sedative or tranquilizer use disorder at Wave 1, 4.8% had a tranquilizer or sedative use disorder while 34.7% had at least one other SUD at Wave 2. CONCLUSIONS: Most adults who engaged in the misuse of prescription tranquilizers or sedatives ceased using within 3 years; however, their prior misuse was associated with higher prevalence of having a SUD three years later.